Acidentes de trabalho na cultura jurídica brasileira: da responsabilidade civil ao seguro social (1919-1944) - Arley Fernandes Teixeira (2023)
This dissertation investigates accidents at work in Brazilian legal culture between 1919 and 1944, taking as its starting point Decree-Law 3.724/1919, the first national legislation on the subject, replaced in 1934 by Decree n. 24.637. The main sources consulted in this work were the books of civil, labor and social security legal doctrine between 1904 and 1944, as well as parliamentary debates between 1919 and 1929, that is, from Decree-Law 3.724/1919 until the last year before the National Congress closed in 1930. From the analysis of these sources, it was possible to conclude that, from the point of view of legal practice, Decree-Law 3,724/1919, in part because of the social pacification movement that guided it since its creation, present in the legislation through mechanisms that made its application difficult, and in part because of the very social structure of Brazil at that time, was underused by Brazilian workers, very different from the scenario found after 1934, with Decree 24,637. Notwithstanding the several attempts to reform the legislation throughout the 1920s, none of the attempts prospered for political reasons, in a perspective that, in the parliamentary debates, polarized the Chamber of Deputies and the Federal Senate. From a theoretical point of view, the period between 1919 and 1944 was the stage of two major shifts that are fundamental for the understanding of the legal nature of accidents at work until today. In the 1930s, during the Vargas period, there was a second shift, this time to the social security field, through discussions about the need to adopt social insurance and the rejection of the model represented by the theory of professional risk.